Understanding Black–White Wage Differentials: 1960–1990 - Heckman, James J; Lyons, Thomas M; Todd, Petra E (American Economic Review, 2000)
Understanding Black-White Wage Differentials, 1960-1990 Author(s): James J. Heckman, Thomas M. Lyons, Petra E. Todd Source: The American Economic Review, Vol. 90, No. 2, Papers and Proceedings of the One Hundred Twelfth Annual Meeting of the American Economic Association, (May, 2000), pp. 344 -349 Published by: American Economic Association Stable URL: http://www.jstor.org/stable/117248 Accessed: 16/08/2008 00:56